Interexaminer reliability of the German version of the DC/TMD - Asendorf, Anne; Möllenkamp, Johanna; Schierz, Oliver; Rauch, Angelika; Asendorf, Thomas; Rammelsberg, Peter; Eberhard, Lydia (Journal of oral rehabilitation, 2021)
Aim - Verification of the interrater reliability of axis I diagnoses of the German version of the DC/TMD. The hypothesis was that the DC/TMD protocol yields comparable results, if examiner instructions are closely followed.
First published: 10 July 2020
Gesehen am 12.01.2022